Placement impact of distributed generation in distribution networks - Nurul Iman, Mat Yatim (2009)
The Distributed Generation (DG) penetration in distribution network has been slowly increasing for the last few years due to advancement of technologies and institutional changes in the electric power industry. DG has gained popularity as it seen to be the reliable option for solving major problem in electric power industry such as reduce high loss, decrease line losses, improving voltage profile at feeders and environmental effect. As the DG was popular, it is in the best interest of all players to allocate the DG to minimize the system losses thus improving voltage profile. This paper aims to find the optimal location for placing DG in distribution network to minimize the total power losses in distribution network, to propose the network improvement based on the presence of DG. The methodology starts with running the distribution load flow program to find the state of the bus systems. The base case load flow was simulated in DigSILENT PowerFactory to find the potential location for placing the DG. The proposed methodology in this paper is using Loss Sensitivity analysis which been applied at the feeder in test systems to find the potential location to place DG in terms minimizing the total power losses in the distribution network.